Model Pengembangan Agribisnis Cabai Berkelanjutan di Provinsi Maluku Utara: Pendekatan SWOT dan Matriks Perencanaan Strategis Kuantitatif (QSPM) - Hasrul A Marsaoly; Munawir Muhammad; Jiswinton Popala (Postgraduate, University of Mataram, 2026)
The cayenne pepper agribusiness plays a vital role in supporting food security and the regional economy, but its development still faces various obstacles, such as price fluctuations, climate change, technological limitations, and weak farmer institutions. This study aims to analyze internal and external factors, determine priority strategies, and develop a sustainable cayenne pepper agribusiness development model in Oba and North Oba Districts, North Maluku Province. The study used a quantitative descriptive approach with Strengths, Weaknesses, Opportunities, Threats (SWOT) and Quantitative Strategic Planning Matrix (QSPM) analyses. Data were obtained through observation, interviews, questionnaires, and documentation of 22 farmers and key informants selected purposively. The results showed that the IFAS analysis produced a total score of 2.64, while the EFAS obtained a total score of 2.58, placing the cayenne pepper agribusiness in Quadrant I (Growth Strategy) with coordinates (0.49; 0.41). The QSPM analysis established priority strategies in the form of strengthening farmer group institutions, increasing production, implementing sustainable cultivation technologies, strengthening marketing networks, and developing partnerships and market access. This research resulted in a Sustainable Chili Pepper Agribusiness Development Model that integrates IFAS, EFAS, SWOT, and QSPM analyses as a conceptual framework in formulating a productive, competitive, and sustainable agribusiness development strategy.